2021
DOI: 10.2196/29744
|View full text |Cite
|
Sign up to set email alerts
|

Falls Detection and Prevention Systems in Home Care for Older Adults: Myth or Reality?

Abstract: There is an exponential increase in the range of digital products and devices promoting aging in place, in particular, devices aiming at preventing or detecting falls. However, their deployment is still limited and only few studies have been carried out in population-based settings owing to the technological challenges that remain to be overcome and the barriers that are specific to the users themselves, such as the generational digital divide and acceptability factors specific to the older adult population. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…While the study presents the first link between cortical activity and sensory reweighting in PD, caution is necessary due to the relatively small sample size and the VR-SOT used in this study 27 . Many VR systems currently on the market (e.g., Bertec®, Virtualis®, UprightVR) or used for research have found the VR-SOT to be reliable compared to traditional SOT 44,45 . Future studies should encompass larger sample sizes, a wider range of PD severities, and subtypes for a more comprehensive understanding how PD affects cortical processes of sensory reweighting.…”
Section: Discussionmentioning
confidence: 99%
“…While the study presents the first link between cortical activity and sensory reweighting in PD, caution is necessary due to the relatively small sample size and the VR-SOT used in this study 27 . Many VR systems currently on the market (e.g., Bertec®, Virtualis®, UprightVR) or used for research have found the VR-SOT to be reliable compared to traditional SOT 44,45 . Future studies should encompass larger sample sizes, a wider range of PD severities, and subtypes for a more comprehensive understanding how PD affects cortical processes of sensory reweighting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a variety of intelligent solutions of ML and DL algorithms, IoT devices, and imaging techniques have been proposed in previous studies to deal with the problem of elderly people falling [15,16]. Intelligent fall detection methods can employ vision, sound, or a wearable device to detect falls.…”
Section: Related Workmentioning
confidence: 99%
“…The evolution of modern technologies developed by researchers to identify and prevent falls in elderly patients has progressed significantly over the past few years. Several sophisticated techniques have been presented to tackle the issue of senior people falling [5,12,13]. These solutions include the use of IoT devices, ML and deep learning algorithms, and imaging training methods.…”
Section: Related Workmentioning
confidence: 99%